EFEKTIVITAS PENGGUNAAN METODE THINK TALK WRITE BERBANTUAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN KEMAMPUAN MENULIS NARASI SISWA - Amelia, Siska Dwi; Iswara, Prana Dwija; Gusrayani, Diah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the narrative writing skills of fourth-grade elementary school students through the application of the Think Talk Write method assisted by audio-visual media. The initial condition showed low ability in developing story ideas, inaccurate use of punctuation and capital letters, as well as limited vocabulary mastery. The study employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, conducted in two cycles, with 20 students as the subjects. Data were collected through observation, questionnaires, and narrative writing tests. The results showed an increase in the average score (on a 100-point scale) from 51.5 in the initial data to 69.75 in the first cycle, and 86.25 in the second cycle. Improvements occurred in content accuracy, idea development, use of punctuation and capital letters, as well as active student participation in learning. Student responses to the implemented learning were positive, with the majority feeling helped in understanding stories and developing ideas. The application of the Think Talk Write method assisted by audio-visual media was effective in improving the narrative writing skills of elementary school students, both in terms of writing quality and active participation.